FORMATION OF VALUE CHAINS IN THE PROCESSING OF LIVESTOCK PRODUCTS - GLUSHKOV, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article is dedicated to studying aspects of forming value chains in processing livestock products. The relevance of the research and the presence of previously unresolved parts of the overall problem determined the purpose of the study, namely to substantiate the role of forming value chains in the processing of livestock products as a factor ensuring food security and economic growth.It is established that livestock farming occupies a leading position in most countries' agro-industrial complex, as it provides the population with valuable food products such as meat, milk, and their derivatives. The article considers global aspects of forming value chains in the processing of livestock products as one of the key sectors of the agro-industrial complex. The study presents current development trends in the dairy and meat sectors and features of their technological processing that determine the competitiveness of products in domestic and international markets.An analysis of global volumes of production, consumption, and trade in dairy and meat products was conducted, which allowed the identification of key growth drivers in the sector and the characteristics of regional markets.The study substantiates the stages of forming value chains in the processing of livestock products, namely primary production, slaughter and primary processing, deep processing, packaging and logistics, marketing and sales, and after-sales services. Each stage creates a separate contribution to the final added value, with the degree of integration of participants in the chain determining the overall efficiency of the processing industry. The research revealed that the intensity of technological processing, the level of innovation, and the degree of integration of chain participants significantly affect the formation of the final product’s value and competitive advantages. It was determined that effective management of value chains in livestock farming is a strategic factor in ensuring food security, economic development, and integrating national agricultural systems into global markets.
Keywords: value chains; processing of livestock products; dairy farming; meat processing; technological processing; agro-food complex; innovations